PENGARUH LITERASI MEDIA SOSIAL TERHADAP KECERDASAN EMOSIONAL IBU RUMAH TANGGA DI KELURAHAN TANJUNG RHU KECAMATAN LIMAPULUH KOTA PEKANBARU - Alda Desi Arisandi Silalahi; Daeng Ayub Natuna; Titi Maemunaty (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The formulation of the problem in this study is how high is the level of social media literacy of housewives in Tanjung Rhu Village, Limapuluh Subdistrict, Pekanbaru City, how high is the emotional intelligence level of housewives in Tanjung Rhu Village, Limapuluh Subdistrict, Pekanbaru City, Is there a positive and significant influence on literacy social media on the emotional intelligence of housewives in Tanjung Rhu Village, Limapuluh District, Pekanbaru City.The purpose of this study was to determine the level of social media literacy of housewives in Tanjung Rhu Village, Limapuluh Subdistrict, Pekanbaru City, to determine the level of emotional intelligence of housewives in Tanjung Rhu Village, Limapuluh Subdistrict, Pekanbaru City, to determine the significant positive effect of social media literacy on intelligence. Emotional Housewives in Tanjung Rhu Village, Limapuluh Subdistrict, Pekanbaru City. This type of research is a quantitative descriptive study of two variables to find the effect between variables, before looking for influence, it is necessary to find a correlation first. The population in this study were housewives in Tanjung Rhu Village, Limapuluh District, Pekanbaru City with 58 samples. There was a significant influence between Social Media Literacy (X) on Emotional Intelligence (Y) Housewives in Tanjung Rhu Village, Limapuluh Subdistrict, Pekanbaru City, which had a large influence of 48%, because there were still 52% determined by other factors that were not part of the this research.Key Words: Social Media Literacy, Emotional Intelligence and Housewives.